Dystrophic Epidermolysis Bullosa in Pregnancy: A Case Report of the Autosomal Dominant Subtype and Review of the Literature - Nicole Colgrove; Rayan Elkattah; Howard Herrell (Case Reports in Medicine)
Epidermolysis bullosa (EB) is a group of inherited blistering skin diseases that vary widely in their pathogenesis and severity. There are three main categories of EB: simplex, junctional, and dystrophic. This classification is based on the level of tissue separation within the basement membrane zone and this is attributed to abnormalities of individual or several anchoring proteins that form the interlocking network spanning from the epidermis to the dermis underneath. Dystrophic EB results from mutations in COL7A1 gene coding for type VII collagen leading to blister formation within the dermis. Diagnosis ultimately depends on the patient’s specific genetic mutation, but initial diagnosis can be made from careful examination and history taking. We present a pregnant patient known to have autosomal dominant dystrophic EB and discuss the obstetrical and neonatal outcome. The paper also reviews the current English literature on this rare skin disorder.